Fatores que influenciam a participação dos pacientes na adesão à higienização das mãos entre profissionais de saúde - Selma de Almeida Pinto (2016)
Hand hygiene has been recommended as a key measure to reduce the transmission of microorganisms that cause infection among patients. However, low adherence to this practice constitutes a major challenge for health services worldwide. Given this reality, the World Health Organization, in 2004, launched the World Alliance for Patient Safety, in order to promote strategies for the prevention of patient injuries arising from healthcare. The first challenge of this alliance was to potentialize actions to improve hand hygiene adherence. In order to achieve this goal several tools were proposed, among them the participation of patients in the Patients for patient safety program. However, despite this recommendation, it can be noted that to date few studies have addressed this issue. In this context, the aim of this study was to identify factors that influence the participation of patients in hand hygiene adherence among health professionals. This was a cross-sectional study conducted with patients and health personnel of the Internal Medicine and Surgical inpatient units of a public general hospital of Belo Horizonte. Data were collected from August to September 2015, through face to face interviews for the application of a structured questionnaire, which were analyzed using the Statistical Package for the Social Sciences statistical program. To characterize the population, a descriptive analysis was conducted and to investigate possible associations between the willingness of the patients to remind the health personnel about hand hygiene and the explanatory variables, the chi-square test was used, in the bivariate associations. In the multivariate analysis, logistic regression was used, considering a statistical significance of p<.05. Of the 250 participating patients, there was a predominance of males (52%); a median age of 54 years; incomplete elementary education (45.2%); retired/sick leave from work (53.6%) and with a monthly income below two minimum salaries (76.4%). Regarding the willingness of the patients to remind the health personnel to wash their hands if they forgot, 65.2% gave positive responses. In the multivariate model an association (p<0.05) was found between the variable age lower than or equal to 54 years (OR= 2.57: 95%CI: 1.49-4.42; p<.005) and no previous hospitalization (OR= 1.74; 95% CI, 1.01-3.00; p<.05). The health personnel of the study, included 83/55.3% nursing technicians; 39/26% nurses and 28/18.7% physicians, the majority were female, with a median age of 35 years and time since professional qualification of <9 years. Of these participants, 83.3% thought that patients could help to improve hand hygiene and 93.3% would like to be reminded about this practice. Regarding the badge Ask me if I washed my hands, 63.3% said they would not like to use it and 20.7% knew the Patients for patient safety program. The findings of this study emphasize the need for educational interventions regarding hand hygiene and initiatives to involve patients in the improvement of hand hygiene adherence. Although the majority of the health personnel responded positively regarding the participation of the patient in reminding them about hand hygiene, they were unwilling to adopt incentive strategies for this attitude, which highlights a gap between their discourse and practice, distancing them from the proposal of the World Health Organization Patients for patient safety program.